Role of glycodeoxycholic acid to induce acute pancreatitis in Macaca nemestrina. Issue 3 (20th March 2022) - Fauzi, Achmad; Suhendro,; Simadibrata, Marcellus; Rani, Abdul Azis; Sajuthi, Dondin; Permanawati,; Amanda, Rosvitha; Makmun, Dadang
Abstract: Background: Acute pancreatitis exhibits a rapid clinical progression which makes it difficult to observe in human; hence, an experimental animal model is needed. This preliminary study performed an induction of acute pancreatitis using glycodeoxycholic acid (GDOC) in an experimental macaque model. Methods: GDOC injections (initial dose of 11.20 mg/kg) were administered in an escalating manner at specific time points. The injection was given along the bilio‐pancreatic duct, followed by measurement of vital signs, serum amylase‐lipase, TNF‐α, procalcitonin, oxidative stress parameters, and microscopic and macroscopic findings. Results: The results indicated that acute pancreatitis occurred following induction with low‐dose GDOC. Serum amylase and lipase levels increased with subsequent GDOC injections. Blood pressure and heart rate were elevated, indicating abdominal pain. Changes in TNF‐α, procalcitonin, and oxidative stress values showed active inflammation. We observed histologic features of pancreatitis and as the dose increased, vasodilation of the splanchnic vasculatures was observed. Conclusions: Small dose GDOC injection in the bilio‐pancreatic duct may have a role to induce acute pancreatitis in Macaca nemestrina .